PENGARUH PEMBERIAN PUPUK KOMPOS CAIR TERHADAP PERTUMBUHAN BIBIT Aquilaria malaccensis - Fujia Astuti; Gusti Muhammad Hatta; Damaris Payung (Universitas Lambung Mangkurat, 2020)
The purpose of this research is to know the effect of liquid compost fertilizer on growth of Aquilaria malaccensis seedlings some parameters of growth such as life percentage, height, diameter increament and number of leaves are measured. Completely randomized design with 5 treatments and 10 replications is used in the research. The reseach result showed that only height and diameter were significant difference among four parameters of growth.Keywords: Influence; compost; naskuru; gaharu